2009
DOI: 10.1007/s10311-009-0212-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nitrification inhibitor dicyandiamide on microbial communities and N2O from an arable soil fertilized with ammonium sulphate

Abstract: Nitrous oxide (N 2 O) affects climate change as a greenhouse gas and indirectly contributes to stratospheric ozone depletion. The main source of N 2 O in soils is denitrification which requires high soil moisture, carbon and nitrate. Nitrification inhibitors can be used to mitigate emissions of N 2 O from soils. In Portugal, fertilisers are often applied when soils are still relatively warm and moist conditions conducive to denitrification. A Portuguese arable soil was inhibited with dicyandiamide, a nitrifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…While this was probably true for UAN without nitrapyrin, a slower nitrification rate with nitrapyrin application was probably due more to the fact that nitrapyrin application reduced the initial population of nitrifiers (as evidenced by the significant lag time at Haubstadt in 2011) and/or slowed nitrifier recovery rather than to whether the absolute quantity of N was sufficient or not. In similar experiments, Carneiro et al (2010) and O’Callaghan et al (2010) found that DCD reduced the nitrification rate because it decreased the NH 4 + –oxidizing microbial population and activity without disrupting their composition and not necessarily because of soil N concentration changes.…”
Section: Discussionmentioning
confidence: 83%
“…While this was probably true for UAN without nitrapyrin, a slower nitrification rate with nitrapyrin application was probably due more to the fact that nitrapyrin application reduced the initial population of nitrifiers (as evidenced by the significant lag time at Haubstadt in 2011) and/or slowed nitrifier recovery rather than to whether the absolute quantity of N was sufficient or not. In similar experiments, Carneiro et al (2010) and O’Callaghan et al (2010) found that DCD reduced the nitrification rate because it decreased the NH 4 + –oxidizing microbial population and activity without disrupting their composition and not necessarily because of soil N concentration changes.…”
Section: Discussionmentioning
confidence: 83%
“…Carneiro et al (2010) pre‐incubated an arable soil with DCD for 45 d. Using phospholipid fatty acid analysis and molecular profiling of NH 3 ‐ and NO$ _2^ - $ ‐ oxidizer communities, they reported that the community structure was not influenced whereas the activity of NH$ _4^+ $ oxidation was strongly reduced.…”
Section: Effect Of Nis On Soil Microbesmentioning
confidence: 99%
“…In 2014, nontreated UAN amounts (Table 5) needed to be increased to 147 kg N ha -1 (8%) and 151 kg N ha -1 (11%) in order to obtain yields similar to pronitridine at 9.4 L ha -1 and nitrapyrin, respectively (Figure 1). The increase in the yield may be due reduced gaseous N loss in the presence of the nitrification inhibitors (Bronson et al, 1992;Zaman et al, 2009;Chen et al, 2010;Halvorson et al, 2010;Carneiro et al, 2010;Khalil, 2011;Di & Cameron, 2012;Burzaco et al, 2013;Omonode & Vyn 2013). This could be because spring conditions generally were wet (Table 3), gaseous N losses in claypan soils as high as 30% have been reported (Wilkison et al, 2000), and summer conditions were favorable for high yields.…”
Section: Precipitationmentioning
confidence: 99%
“…In a recent meta-analysis of enhanced efficiency fertilizers for corn management systems, nitrapyrin or NBPT plus DCD combined with UAN showed no significant effect (P = 0.84) on corn yield data (Cook et al, 2015). However, nitrapyrin and DCD have reduced N 2 O emissions 20 to 90% (Chen et al, 2010;Di & Cameron, 2012;Halvorson et al, 2010;Carneiro et al, 2010;Khalil, 2011;Burzaco et al, 2013;Omonode & Vyn, 2013), which can enhance the efficiency of a UAN application.…”
Section: Uan At 270 Kg N Ha -1mentioning
confidence: 99%